A Solution‐based Method for Synthesizing Pyrite‐type Ferrous Metal Sulfide Microspheres with Efficient OER Activity. Issue 14 (24th June 2020) - Xiang, Wendi; Tian, Qianqiu; Zhong, Cheng; Deng, Yida; Han, Xiaopeng; Hu, Wenbin
Abstract: Simple and stable synthesis of transition metal sulfides and clarification of their growth mechanisms are of great importance for developing catalysts, metal‐air batteries and other technologies. In this work, we developed a one‐step facile hydrothermal approach to successfully synthesize NiS2 microspheres. By changing the experimental parameters, the reason that affects the formation of nanostructured spheres is investigated and discussed in detail, and the formation mechanism of microspheres is proposed innovatively. Furthermore, electrochemical testing results show that the 7 h‐NiS2 catalyst exhibits a remarkable oxygen evolution reaction (OER) activity with an overpotential of 311 mV at 10 mA cm −2 in 1.0 M KOH, superior to precious metal RuO2 . The NiS2 catalyst also exhibits a robust durability. This work will contributes to the rational design and the understanding of growth mechanism of transition metal chalcogenide electrocatalysts for diverse energy conversion technologies. Abstract : NiS2 and CoS2 microspheres were prepared by a one‐step facile solvothermal strategy. In contrast to the conventional approach, this method does not require complex precursors or polluting solvent, and the morphologies of the products are well controlled. Moreover, a growth mechanism of the pyrite‐type disulfides microspheres has been proposed. Electrochemical testing results indicated that the 7 h‐NiS2 microspheres exhibited the best OER catalytic activities with an overpotential of 311 mV to achieve a current density of 10 mA cm −2 in 1.0 M KOH as well as robust long‐term durability.